Bimbingan Aplikasi Matematika NT Algorithms untuk menentukan FPB dan KPK di SMPN Reroroja - Tanti Diyah Rahmawati; Vinsensius H Ndori; Salwiana Salwiana; Agustinus A Ete; Nur Fitriah Safrudin (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The problem that occurs at SMPN Reroroja is that students have difficulty learning mathematics, especially in determining the Greatest Common Divisor (GCD) / FPB and Least Common Multiple (LCM) / KPK. The subject matter is found in mathematics, especially for grade 7 elementary and junior high school students. The subject matter is considered to be for some students because the delivery pattern is still monotonous and less interesting. SMPN Reroroja students also have never studied using technology, including mathematical applications. Therefore, so that learning material about FPB and KPK is not boring and can be understood by students, a new breakthrough is made with the NT Algorthms application guidance activity to make it easier for students to determine FPB and KPK. The results of the questionnaire showed that 92% of students were highly motivated to learn using the NT Algorithms application, while 90% of students were interested in learning using the NT Algorithms application. Thus using the NT Algorithms application is very helpful in the process of learning mathematics and can motivate students.